Establishing continuity in distribution of Diploknema butyracea (Roxb.) H. J. Lam in Indian subcontinent - Majumdar, Koushik; BK, Datta; Shankar, Uma (Journal of Research in Biology, 2012)
The known distribution of Indian Butter Tree (Diploknema butyracea (Roxb.) H. J. Lam) is discontinuous, i.e., in the sub-Himalayan tracts in the north and Andaman and Nicobar Islands in the south. Here, we present the first record of its distribution from Tripura upholding the continuity between the north and the south.